2018
DOI: 10.5114/ceji.2018.81346
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pituitary autoantibodies in idiopathic diabetes insipidus

Abstract: Diabetes insipidus is a disorder resulting from insufficient action of vasopressin (ADH) characterized by excretion of highly diluted urine in large amounts. Idiopathic diabetes insipidus is associated with the presence of both autoantibodies against ADH-secreting neurons and pituitary autoantibodies. The aim of the present study was to evaluate the occurrence of autoantibodies against the pituitary microsomal fraction. The study included 33 sera of diabetes insipidus patients and 10 control sera obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These studies revealed reactivity against 58, 60, 67, 68 and 100 kDa antigens (Sawicka et al 1999). The other studies revealed the presence of M-APA in patients with Hashimoto thyroiditis (60 %), Graves’ disease (72 %), and Addison’s disease (74 %) (Gryczynska and Kosowicz 1991; Gut et al 2007, 2008). This may indicate that the presence of M-APA in patients with different autoimmune diseases and other pituitary problems is relatively common, but still their role is unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies revealed reactivity against 58, 60, 67, 68 and 100 kDa antigens (Sawicka et al 1999). The other studies revealed the presence of M-APA in patients with Hashimoto thyroiditis (60 %), Graves’ disease (72 %), and Addison’s disease (74 %) (Gryczynska and Kosowicz 1991; Gut et al 2007, 2008). This may indicate that the presence of M-APA in patients with different autoimmune diseases and other pituitary problems is relatively common, but still their role is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Sera from five patients diagnosed with autoimmune polyglandular syndrome type II (APS II) with a previous record of the microsomal anti-pituitary autoantibodies confirmed by the same methodology (Gut et al 2008) were included as a positive control. All APS II patients were diagnosed with Addison’s disease and autoimmune thyroid disorder and two of them also suffer from vitiligo.…”
Section: Methodsmentioning
confidence: 99%
“…Idiopathic central DI comprises almost one-fourth of cases [ 7 ]. AVP cell antibodies have been demonstrated in one-third of patients with idiopathic CDI [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…The search of pituitary auto-ags has been very extensive, carried out through different techniques. Indeed, through the immunoblotting on human pituitary, different bands have been revealed in sera from Graves’ disease patients, including those of 49 and 40-kDa [ 33 ]. APAs reactive to a 49-kDa pituitary cytosolic protein were found in 70% of biopsy-proven lymphocytic hypophysitis, 55% of suspected hypophysitis, but also in other diseases including Addison’s disease (42%), and pituitary tumors (20%), as well as in 9.8% of normal subjects [ 34 ].…”
Section: Pituitary and Autoimmunitymentioning
confidence: 99%